Defoliation of Tilia cordata trees associated with Apiognomonia errabunda infection in Finland - Vainio, Eeva; Velmala, Sannakajsa; Salo, Pertti; Huhtinen, Seppo; Müller, Michael (Finnish Society of Forest Science, 2017)
We investigated the causative agent of a disease outbreak affecting small-leaved limes (Tilia cordata Mill.) and resulting in darkening of the leaf petioles and excessive defoliation during summer 2016 in southern Finland. The fungal species composition of the symptomatic petioles was examined by culture isolation and molecular identification using ITS rDNA sequences, which revealed the most prevalent fungal species present in the petioles as Apiognomonia errabunda (Roberge) Höhn. Based on reviewing curated herbarium specimens deposited at the Universities of Helsinki and Turku, A. errabunda is native and widely distributed in small-leaved limes in Finland, and occasionally infects also other broadleaved trees, including Quercus robur L. and ornamental species of Tilia L. and Fagus L. The ITS sequence analysis conducted during this study revealed minor within-species polymorphisms similar to those observed earlier in the Central European and Russian populations of A. errabunda, and reports the first nucleotide sequences of this species from the Nordic countries.
Keywords: Tiliaceae; anthracnose; rDNA; sienitaudit; fungal diseases